Fighting Organized Crime in West Africa: The Case of Community Policing in Ghana - Mills, G.P. (University of Ghana, 2023)
This study utilized a mixed descriptive design approach, incorporating both sequential transformative and concurrent transformative approaches, to examine the impact of community policing on crime prevention and management in various communities in Ghana. Adopting a positivistic paradigm, the study collected data through observations and surveys in the Upper East, Western, Eastern, Volta, and Greater Accra Regions. The sample frame for the study consisted of communities in these regions that have implemented community policing initiatives. The study found that there is a significant level of crime reduction in the target communities, with 31.4% of respondents strongly agreeing and 57.3% agreeing with this statement. The majority of respondents also had confidence in the police (35.1% strongly agreeing and 57.6% agreeing) and believed that the police are friendly and can be relied on for assistance (33.8% strongly agreeing and 59.4% agreeing). In terms of community policing strategies, the study found that visibility strategies, such as decentralizing police posts to communities, and door-to-door visit strategies were particularly effective in improving safety and reducing crime. Overall, the study highlights the importance of community participation and effective community policing strategies in promoting crime prevention and management in target communities.
MA. International Affairs
Keywords: Fighting; Crime; West Africa; Ghana